IJCM_138A: Small group teaching- Perceptions of Students and Faculty of a Medical College in Mangalore, India - Gupta Urbee; Shahi Anshuman; Apurva J. A.; Dayal Prashansa; Jaiswal Harsh; Kumar Nithin; Rekha T; Unnikrishnan Bhaskaran; Mithra Prasanna; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: The demands on Medical Education have greatly increased in the 21st century. For this very reason, there has been an unprecedented growth in the number of medical colleges in India. The teacher's role is to facilitate rather than to direct, to coordinate as much as to communicate. Small group teaching offers students' opportunity to discuss and refine their understanding of complex issues, to problem solve and apply their knowledge to new situations and to reflect on their attitudes and feelings. The study aims to assess the perception of undergraduate medical students regarding small group teaching, the perception of faculty regarding Small group teaching, compare the perception of students on small group teaching, with respect to their academic performance and attendance. Methodology: 93 faculty and 499 undergraduate MBBS students participated in the study and were given a self- administered semi-structured questionnaire. The perception of undergraduate students and teaching faculty on small group teaching was assessed using the 5-point Likert Scale. Independent t-test was applied to find difference in mean perception. Students were categorized based on their academic performance and on their attendance aggregate for the concluded semester. Results: In total, 404 students and 45 faculty members responded thus giving response rates of 80.9% and 48.4% respectively. The overall response rate was 75.8% Conclusion: The study found that both students and faculty members are favorable to the concept of SGT. They found it not only enhances the academic performance of students but also contributes to the personality development of students. Clinical correlations in all the subjects is well appreciated by students and faculty. Suggestions for improvement of SGT such as exam-oriented study, use of innovative and interactive aids can make SGT sessions more effective.